ENVIRONMENTAL INSECURITY IN PAKISTAN: CONTEMPORARY CHALLENGES AND RESPONSES (American International Journal of Humanities, Arts and Social Sciences, 2022)
This study investigates the contemporary environmental risks of air pollution and heat waves, their causes, and their impacts in Pakistan. The research aims to find out the reasons behind the response challenges despite introducing policy programs such as National Climate Change Policy Framework and initiatives like The Billion Tree Tsunami. This study has used a qualitative research approach by adding a case study analysis and an environmental expert’s opinion. The key findings have revealed that compared to the past, the nature of causes behind rising air pollution and intense heat waves has changed. Heavy traffic flow, stop-and-go traffic phenomenon, uncontrolled emissions, and rapid shifts in rainfall are the principal factors that harm Pakistan’s environment. From the expert’s point of view, the study also reveals that the response mechanism is facing hurdles due to institutional dissonance and lack of capacity building. Further, the findings suggest that a multi-layered approach involving policymakers, experts, academicians, and individuals through a community-driven approach can offer practical solutions. As the study has included the example of an individual-level digital response to current environmental threats, this research would provide a platform to make similar budget-friendly and technology-oriented approaches in the future. JEL Classification Codes : Q53, Q54, Q55, Q56, Q58.